Relationship between Sleep Duration and Risk Factors for Stroke - Phua, Chun Seng; Jayaram, Lata; Wijeratne, Tissa (Frontiers in Neurology, 2017)
Stroke is a leading cause of death and disability worldwide. While various risk factors have been identified, sleep has only been considered a risk factor more recently. Various epidemiologic studies have associated stroke with sleep such as sleep duration, and laboratory and clinical studies have proposed various underlying mechanisms. The pathophysiology is multifactorial, especially considering sleep affects many common risk factors for stroke. This review aims to provide an outline of the effect of sleep duration on common stroke risk factors. Appropriate sleep duration especially in patients who have stroke risk factors, and increasing awareness and screening for sleep quality may contribute to primary prevention of stroke.